Pelatihan sales marketing untuk pemasaran jasa melalui promosi dan media sosial untuk menarik calon nasabah di PT. BPRS Madinah Lamongan - Bilgies, Ana Fitriyatul; Finas, Intan Sari; Vironika, Della April (Nur Science Institute, 2025)
The sales marketing training for service promotion through social media at Bank Madinah Lamongan aimed to enhance employees’ understanding and skills in utilizing social media to attract potential customers. This training employed a practical approach, focusing on using platforms such as Instagram, Facebook, and WhatsApp Business to promote financial service products. The methodology included material delivery, case studies, pre-tests and post-tests, and observation of participants’ performance. The results indicated a significant improvement in participants’ comprehension, with average scores increasing by 35% after the training. Participants also showed improved ability in managing social media, demonstrated by increased creativity in promotional content development. However, challenges such as limited time and resources in managing social media remain obstacles to be addressed. This training is expected to enhance Bank Madinah Lamongan’s competitiveness in attracting customers in the digital era. It is recommended that the bank strengthen its digital marketing resources and conduct regular evaluations to ensure the program’s sustainability.